Nontuberculous mycobacterial infections in cystic fibrosis: to treat or not to treat?. Issue 6 (November 2016) - Nick, Jerry A.; Pohl, Kerstin; Martiniano, Stacey L.
Abstract : Purpose of review: The diagnosis of nontuberculous mycobacteria-pulmonary disease (NTM-PD) in cystic fibrosis (CF) is challenging, as it requires both microbiological and clinical evidence in the setting of coexisting airway infections and progressive lung disease. Although in some individuals NTM can accelerate the progression of CF lung disease, in others NTM may remain indolent for years, or appear transiently in sputum cultures. The dilemma faced by clinicians is to accurately identify those patients who are likely to benefit from therapy, while avoiding unnecessary treatment in those with indolent infection. Recent findings: Several recent studies have better defined the characteristics of NTM-PD in the CF population. In addition, consensus recommendations for the evaluation and management of NTM in CF have been published, which reflect the current literature and expert opinion of best practices. Summary: There is currently no marker that is sensitive and specific for the presence of NTM-PD. Instead, the diagnosis in CF requires a systematic review of all aspects of the patients' care. Treatment of identified coinfections and comorbidities must be optimized to accurately assess the clinical impact of the NTM.